Langerhan's cell histiocytosis complicating small bowel Crohn's disease. Issue 2 (February 1996) - Lee-Elliott, C; Alexander, J; Gould, A; Talbot, R; Snook, J A
Abstract : Langerhan's cell histiocytosis is a rare infiltrative disorder of unknown aetiology. A variety of tissues may be affected, but clinically evident intestinal involvement is unusual. An adult patient is described with Crohn's disease of the terminal ileum who subsequently developed Langerhan's cell histiocytosis with extensive infiltration of the small bowel.